Methods to Develop the Language Competence for Future Teachers - Sadikova Salima (Scientific Trends, 2024)
This article discusses effective methods of developing language competence in future teachers and lists a number of useful methods.
Keywords: Language competence, innovative method, active and passive methods, interactive methods, the formation of language competence.